Sex affects immunolabeling for histone 3 K27me3 in the trophectoderm of the bovine blastocyst but not labeling for histone 3 K18ac - Carvalheira, Luciano de R. (PLoS One, 2019)
The mammalian embryo displays sexual dimorphism in the preimplantation period. Moreover, competence of the embryo to develop is dependent on the sire from which the embryo is derived and can be modified by embryokines produced by the endometrium such as colony stimulating factor 2 (CSF2). The preimplantation period is characterized by large changes in epigenetic modifications of DNA and histones. It is possible, therefore, that effects of sex, sire, and embryo regulatory molecules are mediated by changes in epigenetic modifications. Here it was tested whether global levels of two histone modifications in the trophectoderm of the bovine blastocyst were affected by sex, sire, and CSF2. It was found that amounts of immunolabeled H3K27me3 were greater (P = 0.030) for male embryos than female embryos. Additionally, labeling for H3K27me3 and H3K18ac depended upon the bull from which embryos were derived. Although CSF2 reduced the proportion of embryos developing to the blastocyst, there was no effect of CSF2 on labeling for H3K27me3 or H3K18ac. Results indicate that the blastocyst trophoctoderm can be modified epigenetically by embryo sex and paternal inheritance through alterations in histone epigenetic marks.